Investigating Layers of Identity and Identity Gaps in Refugee Resettlement Experiences in the Midwestern United States. Issue 3 (27th May 2019) - Bergquist, Gretchen; Soliz, Jordan; Everhart, Kristen; Braithwaite, Dawn O.; Kreimer, Lee
Abstract : During resettlement, refugees experience changes in personal and community relations that can have dramatic effects on their sense of self and, in turn, well-being. As such, many refugees are forced to reconceptualize their identity as they encounter and integrate into a new host country and culture. Guided by communication theory of identity, interviews ( N = 26) provide insight into personal, relational, enacted, and communal aspects of identity as well as uncovering identity gaps that may differentiate positive and negative personal and relational outcomes for refugees. Findings are framed within an identity pathway model of refugee well-being that we hope provides a guide for inquiries and/or interventions aimed at improving lives and experiences of refugees. Limitations and directions for future research are discussed.